Recurrence of medical errors despite years of preventive measures: A grounded theory study - Aidin Aryankhesal; Negar Aghighi; Pouran Raeissi; Zhila Najafpour (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Despite great efforts to improve patient safety, serious preventable medical errors continue to occur. Accurate rooting causes of error recurrence are essential for reviewing methods to prevent them. This study aimed to identify the main causes of the recurrence of medical errors despite their previous occurrence.MATERIALS AND METHODS: This qualitative study was performed using the grounded theory method, with theoretical sampling from April to July 2021, through semi-structured interviews with 25 experts and treatment staff of hospitals under the auspices of four universities of medical sciences in Iran.RESULTS: Four main parts were identified: 1) primary and secondary factors leading to the occurrence of errors, 2) error prevention policies, 3) causes of error repetition, and 4) contextual factors.CONCLUSION: The attention, seriousness, and commitment of health system managers, from top to bottom, to patient safety are essential for preventing error recurrence. The institutionalization of patient safety education from universities and attention to individual, social, and cultural factors should also be given serious attention.